Short term reduction of left ventricular mass in primary hypertrophic cardiomyopathy by octreotide injections - Gunal, AI; Isik, A; Celiker, H; Eren, O; Celebi, H; Gunal, SY; Luleci, C (British Med Journal Publ Group, 1996)
Growth factors have been shown to be associated with primary hypertrophic cardiomyopathy. Octreotide, a long acting somatostatin analogue, can prevent the stimulating effect of growth factors and decrease the left ventricular mass in patients with acromegaly. In the light of these results, three patients with primary hypertrophic cardiomyopathy were treated with subcutaneous octreotide (50 mu g three times a day during the first week and 100 mu g twice a day for the following three weeks). Initially, two patients were in New York Heart Association class II in and one was in class III. At the end of a four week treatment session all were in class I. There were significant decreases in left ventricular posterior wall thickness, interventricular septum thickness, and left ventricular mass in all three patients. Both left ventricular end diastolic and end systolic diameters had increased in all of the patients at the end of the fourth week. Two of three patients showed improved diastolic filling: their hyperdynamic systolic performance returned to normal. No side effects were observed during octreotide treatment. The considerable improvement obtained with the short term octreotide treatment in patients with primary hypertrophic cardiomyopathy seems promising.
Keywords: hypertrophic cardiomyopathy; octreotide